CONCEPT OF ACTIVITY APPROACH TO IMPROVEMENT EDUCATIONAL PROCESS (Pedagogy of Higher and Secondary Education, 2003)
The article investigates the problem of combining didactic theories with the concept of effective teaching. It has been shown that this combination contributes a lot to both quality of education and raising the scientific lives of theoretical and teaching manuals.